KOLABORASI PERBANKAN SYARIAH DAN BAITUL MAAL WAT TAMWIL (BMT) DALAM PEMBERDAYAAN UMKM - Detri Sulisnaningsih; Chrisna Aji Ferdian Utomo; Salsabilla Kirana Ramadanie (Al-Musthofa: Journal of Sharia Economics, 2021)
Baitul Maal wat Tamwil (BMT) is one of the Islamic microfinance institutions. Existence of BMT is expected to contribute to the development of the real economy such as micro, small and medium enterprises (MSMEs), especially for businesses that do not meet all the requirements to obtain financing from Islamic banking institutions. But there are many obstacles that become barriers to BMT in order to empower the real sector, one of which is the lack of funding so that the necessary support from other parties particularly Islamic banking. Islamic banking in particular bank synergy with BMT in optimizing the real economy can be reached by a strategy in which the Islamic bank linkage program can issue indirectly financing the real sector through BMT so that the Islamic banking market penetration could reach the wider community and beneficial to growth in assets and profits while for BMT cooperation with Islamic banks will provide additional sources of funds for financing offered BMT thus also greater, which would also result in increased revenue BMT.